Low-wear diamond electrode for micro-EDM of die-steel. (7th June 2006) - Suzuki, Kiyoshi; Iwai, Manabu; Sharma, Anurag; Sano, Sadao, Tetsutaro Uematsu
The reduction of electrode wear is very important for high-finish and high-accuracy machining in micro-electrical discharge machining. Electrically conductive CVD diamond has shown almost zero electrode wear, even at short pulse duration of 3 µs. Zero electrode wear is extremely important for maintaining the desired shape. This research involves the investigation into the effect of various EDM parameters on the EDM of die-steel using electrically conductive CVD diamond with respect to electrode wear, efficiency and EDMed surface property. The effect of joule heating due to the high electrical resistivity of electrically conductive CVD diamond was also studied. The results indicate that there is no deterioration of the workpiece surface due to joule heating when EDM is performed using the electrically conductive CVD diamond electrode. An investigation into the factors responsible for the low wear of the CVD diamond electrode leads us to deduce that an accelerated deposition of heat-resolved carbon along with the high thermal stability of the diamond are mainly responsible.